The Role of Human Resource Management in an Organization or Company - Dona Zahra Hasibuan; Nur Ahmadi Bi Rahmani (Penerbit ADM, 2022)
This article aims to determine the role of human resource management in organizations. This paper uses the literature review method (research conducted in libraries) to write about the topic. From the discussion it can be concluded that human resource management has three main functions, namely managerial, operational, and integration to achieve organizational goals. Human resource management includes tasks such as staff procurement, staff development, managing compensation, maintaining occupational safety and health, and manage the relationship between workers and their employers. The main task of human resource management is to increase the contribution of human resources (employees) to the organization. From this it can be understood that all activities of the organization in achieving its objectives depend on the people who manage the organization. Therefore, it is important to manage employees well in order to help the organization achieve its goals